(Re) thinking towards a sustainable analytical chemistry: Part I: Inorganic elemental sample treatment, and Part II: Alternative solvents and extraction techniques - Santana, Ana Paula Reis [Unesp]; Nascimento, Patricia de Andrade; Guimarães, Taciana Guarnieri Soares [Unesp]; Ribeiro Menezes, Iohanna M.N.; Andrade, Daniel Fernandes; Oliveira, Andrea Pinto; Gonzalez, Mario Henrique [Unesp] (Elsevier, 2022)
Currently, there is a huge demand for the development of analytical methods for chemical analysis. Sustainable methods have aroused the interest of researchers in the last years. This paper reviews important technologies for digestion and solid-liquid extraction approaches, with emphasis in emerging greener methods for the elemental analysis of different samples. Analytical technologies such as Microwave-assisted wet digestion (MAWD), Microwave-assisted extraction (MAE), Ultrasound-assisted extraction (UAE), Microwave-induced combustion (MIC), Alkaline treatment, and liquid-liquid extraction and other alternative approaches for inorganic elements are highlighted. Application, advantages and limitations of these methods using diluted acids, ultraviolet radiation, alkaline reagents, less toxic solvents [i.e. deep eutectic solvents (DES) and its subclasses, as well as alternative solvents], and combinationof different technologies are discussed. We also briefly present the role of direct analysis using different spectroscopy techniques such as Laser-induced breakdown spectroscopy (LIBS), Laser ablation coupled to plasma-based techniques (LA-ICP-MS/OES), Raman spectrometry, Near-infrared spectrometry (NIR), and X-ray fluorescence (XRF) which a minimum or no sample preparation. The chemometrics approaches applied for the development of the green analytical chemistry were also mentioned.
(Re)pensando uma química analítica sustentável: Parte I: Tratamento de amostras elementares inorgânicos e Parte II: Alternativa solventes e técnicas de extração
Keywords: Sample treatment; Alkaline solubilization; Ultrasound; Combustion; Acid digestion